Increasing The Character Of Mutual Cooperation And Independence From Elementary School Students - Dyah Puji Ardianasari; Sri Utaminingsih; Su'ad (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Abstract: This study aims to describe the effectiveness of game education in improving the character of mutual cooperation and independence of elementary school students. The type of research used is Research and Development (R&D). The steps in this study are potential problems, data collection, product design, design validation, design revision, product testing and product revision. This research was conducted in class V of SDN Tayuwetan 01. Through observations and interviews, it was found that the character of mutual cooperation and student independence was low and needed development to improve these characters. Thus, through the development of educational games, students can improve the character of mutual cooperation and independence. Keywords: Character Education, Educational Games, Independence and Mutual Cooperation